The Use of the Mind Map Method to Improve the Memory of Grade III Students on the Material of Belief in Angels at the Asy-Syauqi Tenggarong Elementary School - Elia Monika (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The teaching and learning process is essentially a communication process, conveying a message from a source through a specific channel/media to a recipient. The message, source, channel/media, and recipient are all components of the communication process. The message to be communicated is the content of the teachings or instruction contained in the curriculum. The source can be a teacher, a student, another person, or a book author or media producer. The channel is the educational media, and the recipient is either the student or the teacher. The results of this research: After three years as a teacher, this is the first time I have implemented Best Practice with my students. Thank you to the Indonesian Teachers' School for making Best Practice a final assignment for participants. There are still many shortcomings in this Best Practice, and I hope it can be improved in the future. Hopefully, by creating the Assignment Letter on the 10 Angels of Allah SWT, I can... Using the Mind Mapping method, developed by brain development expert Tony Buzan, can be a solution to the problems teachers face in the learning process and can make it easier for students to remember learning materials, thus improving their learning outcomes. The Mind Mapping method can be applied to other learning materials and implemented in other classes.